LAJU PERKEMBANGAN Aedes aegypti PADA BEBERAPA MEDIA YANG BERBEDA - Sudarwati, Tri Puji Lestari (Universitas Nahdlatul Ulama Sidoarjo, 2015)
This research was conducted to determine the pace of development of larvae of Aedes aegypti in some media of water, with the aim of knowing the development of Aedes aegypti mosquitoes from egg to be by looking at the development and physiology. The research was conducted between February and April 2008. The material used is the Aedes aegypti mosquito eggs laid on 3 media: water bath water, sewage, and water ponds. The data obtained were statistically analyzed using SPSS. The development of mosquito larvae in the sewer water is 8.3 days, 21.5 days of pool water, water bath of 24.3 days. Results of statistical analysis of all the observed variables showed that, there is a real difference between the sewage and the pool water and bath water, but the pool water and bath water are not significantly different. It can be concluded that the difference in water media affect the development of larvae of Aedes aegypti. Keywords: Aedes aegypti, water bath, water sewer, water ponds.